MEDICAL AND ORGANIZATIONAL BASES OF THE RESOURCE SUPPORT OF THE REGIONAL OPHTHALMOLOGICAL SERVICE IN THE RUSSIAN FEDERATION: REGULATORY ASPECTS (REVIEW) - A. G. Zabolotniy (Сибирский научный медицинский журнал, 2019)
The aim of the study was to conduct a directed analytical review of the legislative, regulatory and legal framework (RLF), of the special literature on the normative and legal regulation (NLR) and the provision of medical and organizational activities (MOA) of the sectoral and regional ophthalmological service (OphS), the medical establishment (ME) of the health system of Russia (HS).Material and methods. The federal legislative, RLF has been studied on the official websites of the government, the Ministry of Health (MH) of the Russian Federation ((RF), and the health administration authorities (HAA) of the federal subjects of RF, including subordinate regulatory and legal acts. An analytical review of the relevant periodical literature on NLR and the provision of MOA of the sectoral and regional OphS, ME industry has been carried out. Bibliographic, informational and analytical methods, expert assessment method, content analysis were used. Results and discussion. A modern RLF for the provision of MOA of the sectoral and regional OphS, MO of HS is represented by more 100 current documents – orders, decrees and directions, guidelines of MH RF and HAA of the subjects of RF, several hundreds of applications. It was established that the primary regulatory and legal basis for the activities of OphS is considered «Procedures for providing medical care (MC) to the population in case of diseases of the eye, its adnexa, and orbit for adults and children»; Requirements and guidelines for the organization and maintenance of MOA of MO branch (orders of MH of RF N 132н/27.02.2016, N 358/08.06.2016, N 182/20.04.2018). Standards for the provision of MC and clinical recommendations – auxiliary.Conclusion. Analysis of RLF support of OphS MOA in the current three-level HS, since 2012–2014 till present, has shown that the legislative and RLF on NLR and the provision of MOA of OphS the industry as a whole has been created. The main established shortcomings are the lack of a unified conceptual approach and compulsory RLF and medical-organizational mechanism for ensuring and final implementation, as declared by the regulations, in particular, resource support of the activities of regional OphS.